Total knee arthroplasty in patients with hypersensitivity to metals - Innocenti, Massimo (Springer Berlin Heidelberg, 2014)
PURPOSE: We evaluated the risk of hypersensitivity to metals in a population of consecutive subjects undergoing a total knee arthroplasty (TKA). We also proposed a diagnostic pathway to address any sensitivity to metals. We finally presented the mid-term outcomes of a full non allergenic knee implant. METHODS: We developed a protocol based on the medical history, patch testing, and on specific laboratory assays, in order to assess a sensitization to metals. Twenty-four patients (25 knees) with referred or suspected allergy to metals were found in more than 1,000 treated patients, with a mean age of 72.9 years. We proceeded to a radiologic study, a clinical evaluation by the visual analogic scale (VAS), and Knee Society rating system (KSS). In all cases a full anallergic cemented implant with an oxidized zirconium femoral component and an all-polyethylene tibial baseplate was chosen. RESULTS: Four (16.6%) of the 24 patients were considered to be hypersensitive to metals. The mean follow-up was 79.2 months. No patient reported any reaction related to hypersensitivity or complications after TKA. The VAS improved from a mean preoperative value of 7.2 to 1.8 postoperatively; the KSS and the functional score increased from 38 to 91 points and from 39 to 88 points, respectively. CONCLUSIONS: We consider careful research of medical history for metals hypersensitivity crucial, and we perform patch testing and lab assays in case of doubtful sensitization. The choice of a modern hypoallergenic implant may prevent any kind of potential reactions.